The respiratory effects of chloramine-T exposure in seawater acclimated and amoebic gill disease-affected Atlantic salmon Salmo salar L - Leef, MJ; Harris, J; Powell, MD (Aquaculture, 2007)
The aim of the present study was to examine the respiratory effects of chloramine-T, a proposed novel chemotherapeutic treatment for seawater-acclimated Atlantic salmon Salmo salar (L.) affected by amoebic gill disease (AGD). Following a surgical recovery period of 20-24h, fish, both healthy (N = 21) and AGD-affected (N = 13) were exposed to either a 1-hour pulse of seawater containing chloramine-T at a therapeutic concentration of 10mg L - 1 (experimental), or 100ml of sterile seawater (sham-treated controls). Arterial blood samples were repeatedly taken from a dorsal aortic catheter prior to exposure (0h), immediately following exposure (1h) and then at 3, 6, 12 and 24h and various respiratory parameters measured. Results showed that there were no significant effects relating to chloramine-T exposure regardless of disease status. Additional examination of the pH-bicarbonate diagrams confirmed that there was minimal acid-base disturbance in fish exposed to chloramine-T regardless of disease status. Significant changes seen within the examined haematological parameters of both healthy and AGD-affected fish appeared to be related to the repeated withdrawal of blood for analysis of respiratory parameters. Overall these results suggest that the use of chloramine-T in full-strength seawater at the therapeutic concentration of 10mg L - 1 for 1h had no significant respiratory effect in healthy or AGD-affected Atlantic salmon. Additionally, these results help to highlight the potential beneficial use of chloramine-T as a commercial treatment for gill diseased in marine Atlantic salmon. 2007.